1971
DOI: 10.1063/1.1659779
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing Breakdown Measurements of Pyrolytic Aluminum Oxide Films on Silicon

Abstract: Self-healing breakdown techniques are employed to study dielectric breakdown in pyrolytic aluminum oxide films on silicon substrates. The Al2O3 is prepared by chemical vapor deposition at low temperature (300–600°C) using Al isopropoxide as source material. Both weak-spot breakdown and intrinsic breakdown in the absence of weak spots using Au–Al2O3–Si test capacitors are investigated. Intrinsic breakdown field strengths of 7.5×106 V/cm for Si+ on p-type substrates and 6.9×106 V/cm for Si − on n-type are observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…While nano-SiO 2 particles, possessing high water absorbing capacity, provide sufficient OH -/O 2anions for STO thin films and improve the efficiency of the anodic oxidation. Moreover, it is well known that the AAO film is a high quality dielectric material with the breakdown strength up to about 700-1000 MV/m [34,35]. Therefore, nano-SiO 2 particles significantly improve the breakdown strength of STO films.…”
Section: Xps As a Powerful Technology To Investigate The Chemical Comentioning
confidence: 99%
“…While nano-SiO 2 particles, possessing high water absorbing capacity, provide sufficient OH -/O 2anions for STO thin films and improve the efficiency of the anodic oxidation. Moreover, it is well known that the AAO film is a high quality dielectric material with the breakdown strength up to about 700-1000 MV/m [34,35]. Therefore, nano-SiO 2 particles significantly improve the breakdown strength of STO films.…”
Section: Xps As a Powerful Technology To Investigate The Chemical Comentioning
confidence: 99%
“…We substitute ~/d = B accordingly and obtain for the field at the maximum of the distribution F (l/E) 9 In (r~/noOd) [4] Curve-fitting also yields the quantity In (noO/rB) from which no can be calculated. However, since the relative scatter in B and in In (noO/rB) is of the same magnitude, the precision with which no itself is determined is very low.…”
Section: (1 --N(vi)t/n) = 1 --Noo Exp (Birt)t/nmentioning
confidence: 99%
“…Their results, differing in breakdown level, have in common a decrease of the breakdown field with increasing layer thickness. Carries and Duffy (9), however, showed that the breakdown field of aluminum oxide films deposited on silicon substrates by the pyrolysis of aluminum isopropoxide and measured with the nonshorting breakdown technique (10) is essentially independent of thickness in the range from 200 to 6000A and is equal to 7.5 • 106 V/cm (Si positive on p-type substrate). Carries and Duffy (9), however, showed that the breakdown field of aluminum oxide films deposited on silicon substrates by the pyrolysis of aluminum isopropoxide and measured with the nonshorting breakdown technique (10) is essentially independent of thickness in the range from 200 to 6000A and is equal to 7.5 • 106 V/cm (Si positive on p-type substrate).…”
mentioning
confidence: 99%
“…In our previous work [12,13], we found that the sol-gel-derived amorphous aluminum oxide (AmAO) film as an excellent dielectric medium with very high breakdown strength [14][15][16][17] can also behave as an effective solid-state electrolyte satisfied the requirement of the self-healing reaction (anodic oxidation) under high electric field at the mean time. The structures of the AmAO film and the Al film are propitious to the transport of both cations and anions involved in the anodic oxidation.…”
Section: Introductionmentioning
confidence: 99%